Using a Free Permit Rule to Forecast the Marginal Abatement Cost of Proposed Climate Policy - Meng, Kyle C. (American Economic Review, 2017)
This paper develops a method for forecasting the marginal abatement cost (MAC) of climate policy using three features of the failed Waxman-Markey bill. First, the MAC is revealed by the price of traded permits. Second, the permit price is estimated using a regression discontinuity design (RDD) comparing stock returns of firms on either side of the policy's free permit cutoff rule. Third, because Waxman-Markey was never implemented, I extend the RDD approach to incorporate prediction market prices which normalize estimates by policy realization probabilities. A final bounding analysis recovers a MAC range of $5 to $19 per ton CO 2 e. (JEL G12, G14, Q52, Q54, Q58)